(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The present study aims at investigating the Ayyubid figure, Al-Naser Ad-Din Muhammad ibn Asad Ad-Din Shirkuh, who had to some extent helped in strengthening the Ayyubid domination over Egypt and the region of the Levant through his efforts in the army as one of the leaders during the reign of his cousin Saladin and providing him with military advice in several situations. He had also played a significant role in running provinces of the government in Homs, including Rahba, Selmayah, and other regions. The study also explores his life, place of birth, growth, date of death, and the various narratives related to the causes of his death. The study reached a set of results, the most prominent of which was that Nasser Al-Din Muhammad bin Asad Ad-Din Shirkuh resorted to reason most of the time in order to obtain the approval of his cousin, Sultan Saladin Yusuf, who owned many fiefdoms in the Levant.